2016
DOI: 10.5472/mmjsi.2902.02
|View full text |Cite
|
Sign up to set email alerts
|

Asthma COPD overlap syndrome (ACOS)

Abstract: Asthma and chronic obstructive pulmonary disease (COPD) are the two most prevalent obstructive diseases of the lung. Although asthma and COPD differ in many ways some properties of each disease co-exist in some patients, particularly in patients with advanced age which recently brought up the term; Asthma-COPD Overlap Syndrome (ACOS). In addition to the fact that clinical trials deliberately exclude the patients in this group, the diagnostic criteria of ACOS are not well established. Both of these factors cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…However, real life data have shown that some patients can occasionally have features of both diseases, and this condition has been termed the asthma-COPD overlap syndrome (ACOS). This new terminology is discussed by Dr.Kocakaya in this issue [1].…”
mentioning
confidence: 99%
“…However, real life data have shown that some patients can occasionally have features of both diseases, and this condition has been termed the asthma-COPD overlap syndrome (ACOS). This new terminology is discussed by Dr.Kocakaya in this issue [1].…”
mentioning
confidence: 99%